Propedeutics of Internal Medicine. Section 1 : Collection of tests for the third-year foreign students specialty: 222 "Medicine" - Lukashenko, L.V.; Likhasenko, I. V.; Oleynik, O. I.; Avramenko, N. F.; Lysenko, V. A.; Zhemanuk, S. P.; Лукашенко, Ланна Віталіївна; Лихасенко, Іветта Валеріївна; Олійник, Олександр Іванович; Авраменко, Наталя Федорівна; Лисенко, Владислав Андрійович; Жеманюк, Світлана Павлівна (My University, 2022)
The academic discipline "Propedeutics of Internal Medicine" includes mastering to conduct questioning and physical examination of patients and analyze their results in the clinic of internal medicine; investigate the results of basic laboratory and instrumental methods of research; define leading syndromes and symptoms in the clinic of internal diseases. The main objectives of the discipline "Propedeutics of Internal Medicine" is the teaching methods of examination of patients, recognition of basic clinical syndromes building syndromal diagnosis doctoral foundations of ethics and deontology. Interdisciplinary connections: discipline "Propaedeutics of Internal Medicine" based and integrates with subjects: normal anatomy, topographic anatomy, pathological anatomy, normal physiology, pathological physiology, pharmacology. The collection of tests is intended for preparation for the semester final test and covers all topics from Module 1.